Algebraic quotients and Geometric Invariant Theory - Medina García, Nélida (2020)
The quotient of an algebraic variety by action of an algebraic group does not always has a variety structure. The aim of this work is to describe a methodfor constructing good quotients, in the sense of Geometric invariant theory, in algebraicgeometry.